Epidemiology and management of ventral hernia in a tertiary health care centre- a prospective observational study - Gaur, Sourabh; Sharma, Dharamanjai K. (International Surgery Journal, 2022)
Background: Ventral hernias are a common problem confronting surgeons. Data about standards of their surgical management have failed to keep pace with rapid advances in surgical techniques, and materials. Older techniques have often been discarded simply because of availability of newer ones without due consideration to availability, feasibility, training, local conditions and constraints. Therefore, a balanced, practical and pragmatic opinion regarding surgical management at individual, institutional and regional levels is needed. We studied clinical aspects and best treatment modalities of ventral hernias in our set-up. Methods: This is a prospective observational study of various types of ventral hernias, surgically managed at a tertiary care hospital between January 2018 and September 2019. Results: Mean age of presentation among 71 patients (27 males, 44 females) was 48.11±5.71 years. Incisional hernias (30.98%) were the commonest type. Painless swelling (49.29%) was the most common clinical presentation. Obesity (40.84%) and multiparity (30.98%) were the most common associated risk factors. Incisional hernias are probably better managed by open approach. Conclusions: Ventral hernias are more prevalent in the elderly and females. Incisional, umbilical, epigastric hernias are the more common types. Laparoscopy is being preferred over open procedure due to some advantages that it offers, but incisional hernias can often be better managed by open approach depending upon local set up. In addition, laparoscopic approach is not universally applicable and also has certain drawbacks.